Improving Mathematics Learning Outcomes Through the Consideration Model for Class VII Students - Fitriah, Fitriah; Akorede, Asanre; Agyei, Emmanuel (Interval: Indonesian Journal of Mathematical Education, 2023)
Purpose of the study: The current research aims to determine student learning outcomes in class VII which are improved through the application of a decision-making model, namely the consideration model. Methodology: This research uses the classroom action research method, the sample involved in this research is class VII students. There are several research procedures that will be carried out, namely: planning, action, observation, and reflection. The quantitative data analysis technique is descriptive statistical analysis, while qualitative data is assessed verbally when observing the learning process. Main Findings: Based on the results of research and descriptive analysis, the average value of mathematics learning outcomes after implementing the Consideration Model in cycle I was 64.80. Meanwhile, the average value of learning outcomes after implementing the Consideration Model in cycle II was 77.83. Class VII students' mathematics learning outcomes have increased. This increase is caused by the learning techniques used which can increase student activity and reduce student tension in learning mathematics. Novelty/Originality of this study: Previous research aimed to determine the model of consideration and value clarification in improving affective abilities. Meanwhile, this research is new in improving students' mathematics learning outcomes through the consideration model.